PENYULUHAN TENTANG PEMBANGUNAN RUMAH SISTEM PANGGUNG UNTUK MENGURANGI DAMPAK AIR PASANG/BANJIR DI KOTA BANJARMASIN - Fathurrahman Fathurrahman; Abdurrahman Abdurrahman (Universitas Islam kalimantan MAB, 2017)
Since many years ago, house building with stage system has been known by Kalimantan society, especially the society of South Kalimantan and here the benefits of the house with stage system are introduced. In the past, the main benefit of the stage system was to avoid attack of wild animals, so the height of the house could reach 250 cm. Beneath the house, people could do routine activities such as pounding paddy and children could play if the soil under the house was dry. In the introduction of the house benefits, it is explained that if backfilling for the house is conducted, the volume of the backfilling in the form of material, gravel, sand, and soil do not add the volume of water which comes due to tide and rain with long duration and high intensity. Volume plays important role in the increase of the overflowing water. The volume causing the increase of overflowing water can be obtained by multiplying the area of a house and its height if all house buildings do not utilize stage system. The lecture in this socialization is shown by using demonstration tool in the form of vessel which contains water, so if a solid item is put in the vessel, the surface of the water inside the vessel will rise.